Penilaian Kesehatan Bank Syariah - Al Farid, Hazwin; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
This writing discusses the health assessment of Sharia Banks. The legal basis for regulating the health assessment of Sharia Banks (BUS and BPRS) refers to the regulations of the Law, PP, PBI, POJK, and BI, as well as OJK circulars. The article explains the RGEC assessment of Sharia Banks, using a qualitative approach with a literature study research design. This writing presents a literature review of various sources related to assessing the health of Sharia Banks, the legal basis of BUS and BPRS, and RGEC. The discussion explains that bank health assessment reflects the bank's performance and is the result of assessing the bank's condition to overcome risks and improve performance. The logical structure and causal connections between statements ensure a clear and balanced presentation of the topic. The health assessment of Sharia Commercial Banks (BUS) is regulated by Law Number 21 of 2008 concerning Sharia Banking. According to this law, banks are required to maintain their level of soundness. Article 1, paragraph 6 of POJK No. 8 of 2014 pertains to the evaluation of the soundness level of sharia commercial banks and sharia units. The health assessment of Sharia Rural Banks (BPRS) is regulated by Bank Indonesia Regulation No.9/17/PBI/2007, which is based on the Health Assessment System Rural Credit Bank using Sharia Principles. The RGEC method is an advancement of the CAMELS method. The RGEC method involves inherent risks, and quality risk management is applied to bank operations across eight factors: credit risk, market risk, liquidity risk, operational risk, legal risk, strategic risk, compliance risk, and reputation risk.